Al-Kitāb wa Al-Qur’ān: Qirā’ah Mu’aṣirah - Inayatul Mustautina (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2020)
In KBBI, clothing means what items are worn (clothes, pants and so on). As is well known that when talking about clothing it will also be discussed about genitals and headscarves or hijab. Muhammad Syahrur argues that the word al-hijab in the Qur'an is mentioned eight times, which is interpreted as shar'i clothing and none of them refer to libas. The concept or rules of men's clothing and women's clothing must be different, because the limits of male and female genitalia are also different. This is stated in the Al-Quran, one of which is in the verse an-Nur verse 31. In this paper, the author will discuss how M. Syahrur interpreted the verse in accordance with the theory of boundaries and views associated with other Qur'anic verses.